Discovery and antibacterial study of potential PPK1 inhibitors against uropathogenic E. coli. (1st January 2020) - Peng, Liang; Zeng, Liting; Jin, Hongwei; Yang, Lixin; Xiao, Yi; Lan, Ziquan; Yu, Zhanpeng; Ouyang, Shi; Zhang, Liangren; Sun, Ning
Abstract: Novel antibacterial agents are urgently needed to address the infections caused by multi-drug resistant bacteria. Urinary tract infections are common infectious diseases in clinical. Most of these infections are caused by drug-resistant uropathogenic Escherichia coli . PPK1 is an essential kinase for bacterial motility, biofilm formation, quorum sensing, and virulence factors in the expression of uropathogenic E. coli . In the present study, two small molecules potentially targeting PPK1 were discovered through virtual screening and biological assays. The in vitro and in vivo results suggested that the interaction of these compounds with PPK1 can disrupt biofilm formation of uropathogenic E. coli and reduce invasive ability and resistance to oxidative stress of this strain. Moreover, the compounds exhibit good antibacterial bacterial activity in the mice with urinary tract infection. Taken together, our findings could provide a new chemotype for the development of antibacterials targeting PPK1. Graphical Abstract: UF0001